The experience of “non-I” in the perspective of the experience of man in Karol Wojtyła’s adequate anthropology - Mruszczyk, Magdalena (Folia Philosophica, 2010)
Working out the experience of a man as both starting point and research method of philosophical anthropology, Karol Wojtyła conjoined two seemingly separated and contradicting philosophical stances: metaphysics and phenomenology. This new method was expressed in a theory of the experience of man (person) taken as phenomenological experience, rooted in a conscious experience of knowing subject which, as a person, is faced with themselves as both subject and object. This insight - itself a kind of self-recognition of particular man, based on their personal experience understood along such lines - appears as ultimate moment of the experience of man. Simultaneously, this kind of personal experience allows an overall experience gathering in itself three kinds of experience and different cognitive attitudes. Taking this idea as granted, the experience of the „other” shows up as the experience of „non-I”, which makes it necessary to justify one’s own presence in the area of the experience of man and explaining its methodological uniqueness.